Gyrinus aquiris LeConte 1868 - Majka, Christopher; Kenner, Rex (Zenodo, 2009)
Gyrinus aquiris LeConte, 1868 Gyrinus aquiris was reported from New Brunswick by Oygur and Wolfe (1991) and Roughley (1991) and from Nova Scotia by Campbell et al. (1987) (Fig. 8). In Nova Scotia it has only been found on Cape Breton Island (Fig. 2). Although Roughley (1991) reported it from Prince Edward Island, Majka (2008) removed it from the province’s faunal list since there are no voucher specimens or published records. Morrissette (1979) reported the species from ponds and lakes invaded by aquatic plants. Oygur and Wolfe (1991) reported 80% of specimens from lentic habitats. Published as part of Majka, Christopher & Kenner, Rex, 2009, The Gyrinidae (Coleoptera) of the Maritime Provinces of Canada: new records, distribution, and faunal composition, pp. 355-372 in ZooKeys 22 (22) on page 362, DOI:10.3897/zookeys.22.216, http://zenodo.org/record/576544